The Position and Revitalization of Customary Criminal Law in the Perspective of National Criminal Law - Nurhidayatullah, Muhammad Ali; Simanjuntak, Takkas Marudut (PDIH Untag Semarang, 2024)
This research aims to describe and analyze the status of customary law in Indonesia and the revitalization of customary criminal law from the perspective of Indonesian criminal law. This study employs normative legal research methods by analyzing various literatures. The research approach used is based on legislation, utilizing secondary data consisting of primary legal materials, secondary legal materials, and tertiary legal materials, presented in a qualitative descriptive manner. The results indicate that although official authorities such as the police and courts remain significant, customary institutions often serve as the first point of mediation for resolving conflicts within communities, especially in cases involving minor material losses and other issues rooted in local concerns. This suggests that traditional values and culture hold an important place in society and influence how people interact with the formal legal system. Additionally, the revitalization of customary law is necessary, particularly in the recognition of customary legal norms, which is crucial for creating an optimal balance between modernity and the preservation of traditional values. This contributes positively to justice, welfare, and cultural sustainability in Indonesia